2021
DOI: 10.3390/ijms22062965
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes during Pregnancy: A Maternal Disease Complicating the Course of Pregnancy with Long-Term Deleterious Effects on the Offspring. A Clinical Review

Abstract: In spite of the huge progress in the treatment of diabetes mellitus, we are still in the situation that both pregestational (PGDM) and gestational diabetes (GDM) impose an additional risk to the embryo, fetus, and course of pregnancy. PGDM may increase the rate of congenital malformations, especially cardiac, nervous system, musculoskeletal system, and limbs. PGDM may interfere with fetal growth, often causing macrosomia, but in the presence of severe maternal complications, especially nephropathy, it may inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 244 publications
(414 reference statements)
6
126
1
9
Order By: Relevance
“…Table 2 shows the differences between the two groups throughout the course of pre-gestational diabetes during pregnancy. Maternal age at diagnosis of the disease was significantly higher in the HbA1c ≤ 7% group than in the group with HbA1c > 7%, 26.00 (18.0-32.00) vs. 20.00 (12.50-27.00). Women with HbA1c ≤ 7% compared with those with HbA1c > 7% reached, at term of pregnancy, significantly lower levels of HbA1c, 5.80 (5.70-6.00) vs. 6.70 (6.30-7.25).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Table 2 shows the differences between the two groups throughout the course of pre-gestational diabetes during pregnancy. Maternal age at diagnosis of the disease was significantly higher in the HbA1c ≤ 7% group than in the group with HbA1c > 7%, 26.00 (18.0-32.00) vs. 20.00 (12.50-27.00). Women with HbA1c ≤ 7% compared with those with HbA1c > 7% reached, at term of pregnancy, significantly lower levels of HbA1c, 5.80 (5.70-6.00) vs. 6.70 (6.30-7.25).…”
Section: Resultsmentioning
confidence: 87%
“…Most studies on this topic in the literature have compared type 1 versus type 2 diabetes, showing a worsening of diabetes-related complications during pregnancy, reporting a trend of higher maternal glucose levels, higher rates of preterm births, and of LGA babies in women with type 1 diabetes compared with type 2 diabetes [ 2 , 26 ]. By contrast, women with type 2 diabetes tend to be older, have higher rates of obesity, greater ethnic diversity, and greater socioeconomic deprivation [ 21 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this disease is associated with both short-term (perinatal) and long-term complications in the mother and the newborn. Long-term complications include an increased risk of developing type 2 diabetes (T2D) and obesity later in the mother’s and baby’s life, revealing the adverse intergenerational effects of GDM [ 4 , 8 , 9 , 10 ]. This is related to the theory of Developmental Origins of Health and Disease (DOHaD) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, total and parenteral carbohydrate intakes were linked to smaller aortic annulus of the LV outflow tract, and hyperglycemia in the neonatal period was associated with increased LV wall thickness at a 6-year follow-up. Fetal adaptations to hyperglycemia include hypertrophy of the interventricular septum [31] and shorter and narrower ventricles [32], and children to mothers with pregestational diabetes have been reported to exhibit left ventricular hypertrophy [33]. Hyperglycemia in preterm neonates has also been reported to be associated with cardiac septal hypertrophy and right ventricular dysfunction [11].…”
Section: Discussionmentioning
confidence: 99%
“…While reduced length of the LV has been described as an early life adaptation to hyperglycemia [32], an explanation for an elongation of the left atrium associated with hyperglycemia is lacking. Previous studies of the diastolic filling pattern indicated a stiffer LV wall in children born extremely preterm than in control children born at term [3].…”
Section: Discussionmentioning
confidence: 99%